GARNET FRACTIONATION IN A HYDROUS MAGMA OCEAN AND THE ORIGIN OF AL-DEPLETED KOMATIITES: MELTING EXPERIMENTS OF HYDROUS PYROLITE WITH REES AT HIGH PRESSURE - Inoue T.; Rapp R.P.; Zhang J.; Gasparik T.; Weidner D.J.; Irifune T. (My University, 2000)
Melting experiments of a representative mantle composition doped with some key trace elements were conducted under hydrous conditions at pressures to 20 GPa. The results demonstrate that only ~5-25% of garnet fractionation and relatively low pressures (<8 gpa) and low temperatures (~1300-1500°C) are required to produce Al-depleted Barberton-type komatiites (>3.5 Ga) in the solidifying hydrous magma ocean. This suggests that the Archean mantle was much cooler than so far believed from the origin of the komatiites based on anhydrous experiments.
Keywords: KOMATIITE; MELTING; ARCHEAN; RARE EARTHS; GARNET GROUP; FRACTIONAL CRYSTALLIZATION; Precambrian::Archean; Докембрий::Архей